The participation of fisherman wives in improving the domestic Income in korong sungai limau padang pariaman regency, the Province of west sumatera - Heri Oktofriyadi; Firman Nugroho; Kusai ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted on December 2013. It was aimed at finding out theinvolvement of fisherman wives in terms of time allocated to increase the domestic incomesand the their participation in terms of domestic incomes. The method used in this study wascensus method with 22 respondents.The fisherman wives involvement observed from the number of working hoursdevoted to increase the domestic incomes shows that the fishermen’s working hours is higherthan their wives. The wives contribution to the domestic income by average contribution onthe level of 26-50 %.Keywords: Fisherman’s wives participation, income participation of fisherman’s wives, DesaKorong Sungai Limau.